1999
DOI: 10.1063/1.125275
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic theory of stress distribution in epitaxial Pb(Zr, Ti)O3 thin films

Abstract: Reciprocal space mapping of phase transformation in epitaxial PbTiO 3 thin films using synchrotron x-ray diffraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 9 publications
(9 reference statements)
1
37
0
Order By: Relevance
“…oxygen content in the films) during film growth; they suggested that crystal volume expansion by oxygen vacancies (V O ) could suppress the degree of the strain gradient (figure 3b). According to a general model for the strain profile [38], independent of the actual relaxation mechanism, the strain u(z) in epitaxial thin films can be expressed as…”
Section: (B) Strain Gradient and Its Engineering At Nanoscalementioning
confidence: 99%
“…oxygen content in the films) during film growth; they suggested that crystal volume expansion by oxygen vacancies (V O ) could suppress the degree of the strain gradient (figure 3b). According to a general model for the strain profile [38], independent of the actual relaxation mechanism, the strain u(z) in epitaxial thin films can be expressed as…”
Section: (B) Strain Gradient and Its Engineering At Nanoscalementioning
confidence: 99%
“…An exponential profile over the thickness for the stress has been considered in several models [147] and compared to experimental variation with thickness of the lattice parameters for Pb(Zr 0.4 Ti 0.6 )O 3 [147]. Catalan et al [148] have used this exponential decay of the strain and X-ray diffraction analysis to calculate the strain profile.…”
Section: Thickness Dependent Relaxationmentioning
confidence: 99%
“…If the stress relaxation due to the misfit dislocations is negligible, the strain profile can be written as ‫ץ‬u 1 / ‫ץ‬z =−u 10 / ␣ 2 and ‫ץ‬u 2 / ‫ץ‬z =−u 20 / ␣ 2 . 9,11 In this letter, the misfit dislocations are assumed to provide the main relaxation mechanism, and the strain profiles as a function of z are given bywhere ␣ 1 and ␣ 2 are decline parameters that measure the penetration depth of the strain. u 10 and u 20 are the strains at the upper and lower film-substrate interfaces, respectively.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] In this letter, we report on our investigation of the effects of the strain gradient caused by the epitaxial stresses in ferroelectric thin films ͑FTFs͒ sandwiched between two different substrates. Following the Landau-Ginzburg-Devonshire ͑LGD͒ theory, a general model that includes effects of flexoelectricity and stress gradient is formulated and applied.…”
mentioning
confidence: 99%
See 1 more Smart Citation